Evaluation of the Influence of Selective Beta-Adrenoblockers on the Indicators of the Daily Arterial Pressure Profile in Patients Hypertension - Yarmukhamedova S.Kh; Amirova Sh.A (Genius Journals, 2022)
Hypertension remains one of the urgent problems of medicine. Leading to the development of complications, arterial hypertension is accompanied by the development of structural and functional changes in the heart. The study of insufficient reduction in blood pressure is important. At the same time, at present, using the method of daily monitoring of blood pressure, it has been established that with an insufficient nightly decrease in blood pressure, arterial hypertension is characterized by certain and very significant features of the course, prognosis and pathogenesis. At present, it seems quite reasonable to assume that in patients with uncomplicated hypertension and insufficient nocturnal BP reduction, the use of drugs with sympatholytic activity, that is, beta-blockers, may be especially effective.
Keywords: daily arterial pressure profile; patient; Bisoprolol; monotherapy